Autism and Epilepsy in Patients With Tuberous Sclerosis Complex - Specchio, Nicola; Pietrafusa, Nicola; Trivisano, Marina; Moavero, Romina; De Palma, Luca; Ferretti, Alessandro; Vigevano, Federico; Curatolo, Paolo (Frontiers in Neurology, 2020)
Introduction Individuals with Tuberous Sclerosis Complex (TSC) are at increased risk of developing both epilepsy and autism spectrum disorder (ASD), but the relationship between these conditions is little understood. We reviewed published reports to elucidate the relationship between ASD, epilepsy, and TSC and to define the genetic, and neurological risk factors. Methods Articles (January 2004–May 2019) were identified via PubMed, EMBASE, and CENTRAL databases. Article inclusion required report on individuals with TSC-associated ASD and epilepsy with prevalence, odds ratio, or rate report on the comorbidity of ASD in epileptic patients due to TSC. Results A total of 841 abstracts were identified in the original search. Thirty-six articles were included, which identified study populations, ASD measures used, and study confounders as bias factors. This review included 2666 TSC patients, with a mean age of 15.9years (range 1.94–30.3 years). The percentage of TSC patients with epilepsy and autism was 33.7%. Patients with TSC and autism showed more frequent seizures and earlier epilepsy onset than TSC patients without autism. ASD and intractable epilepsy were both predicted by a higher number of areas with dysplastic features revealed in brain MR scans. ASD, the onset of seizures in children <2 years of age, and >3 tubers have all been associated with an increased risk of refractory epilepsy in TSC patients. However, the direction of the relationship is not clear because a history of epilepsy, or infantile spasms in patients with TSC is also associated with an increased likelihood of ASD. Overall, 73.2% of patients carried TSC2 genetic variant and, among patients with TSC and autism, the percentage of TSC2 individuals was 85.6%. Conclusions The complex interrelationship between TSC, autism, and epilepsy, coupled with limited knowledge on the neurobiological basis for the interrelationship, limits overall understanding and opportunities for management. The results of this review highlight the need for early identification, and management to optimize favorable outcomes in the most vulnerable individuals with TSC. Regardless of whether studies are considered individually or collectively, interpretation is made difficult due to the differences between the studies, most notably between methods and diagnostic criteria used to assess intellectual ability.